Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Flower bud proteome reveals modulation of sex-biased proteins potentially associated with sex expression and modification in dioecious Coccinia grandis - Devani, Ravi Suresh; Chirmade, Tejas; Sinha, Sangram; Bendahmane, Abdelhafid; Dholakia, Bhushan B.; Banerjee, Anjan Kumar; Banerjee, Jayeeta (BMC Plant Biology, 2019)
BackgroundDioecy is an important sexual system wherein, male and female flowers are borne on separate unisexual plants. Knowledge of sex-related differences can enhance our understanding in molecular and developmental processes leading to unisexual flower development. Coccinia grandis is a dioecious species belonging to Cucurbitaceae, a family well-known for diverse sexual forms. Male and female plants have 22A+XY and 22A+XX chromosomes, respectively. Previously, we have reported a gynomonoecious form (22A+XX) of C. grandis bearing morphologically hermaphrodite flowers (GyM-H) and female flowers (GyM-F). Also, we have showed that foliar spray of AgNO3 on female plant induces morphologically hermaphrodite bud development (Ag-H) despite the absence of Y-chromosome.ResultsTo identify sex-related differences, total proteomes from male, female, GyM-H and Ag-H flower buds at early and middle stages of development were analysed by label-free proteomics. Protein search against the cucumber protein sequences (Phytozome) as well as in silico translated C. grandis flower bud transcriptome database, resulted in the identification of 2426 and 3385 proteins (FDR <= 1%), respectively. The latter database was chosen for further analysis as it led to the detection of higher number of proteins. Identified proteins were annotated using BLAST2GO pipeline. SWATH-MS-based comparative abundance analysis between Female_Early_vs_Male_Early, Ag_Early_vs_Female_Early, GyM-H_Middle_vs_Male_Middle and Ag_Middle_vs_ Male_Middle led to the identification of 650, 1108, 905 and 805 differentially expressed proteins, respectively, at fold change >= 1.5 and P <= 0.05. Ethylene biosynthesis-related candidates as highlighted in protein interaction network were upregulated in female buds compared to male buds. AgNO3 treatment on female plant induced proteins related to pollen development in Ag-H buds. Additionally, a few proteins governing pollen germination and tube growth were highly enriched in male buds compared to Ag-H and GyM-H buds.ConclusionOverall, current proteomic analysis provides insights in the identification of key proteins governing dioecy and unisexual flower development in cucurbitaceae, the second largest horticultural family in terms of economic importance. Also, our results suggest that the ethylene-mediated stamen inhibition might be conserved in dioecious C. grandis similar to its monoecious cucurbit relatives. Further, male-biased proteins associated with pollen germination and tube growth identified here can help in understanding pollen fertility.
Keywords: Coccinia grandis; Dioecy; Pollen fertility; proteomics; Sex modification; Stamen arrest

Cloning and expression of antibody fragment (Fab) I: effect of expression construct and induction strategies on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Tungekar, Aatir A.; Gani, Kayanat; Bhambure, Rahul (Biochemical Engineering Journal, 2021)
Dual promoter expression constructs offer time and cost-effective alternatives to produce multi-domain proteins like antibody fragments. This investigation is focused on understanding the effect of expression construct (dual promoter vs. co-transformation strategy), codon optimization, and induction strategies on yield and expression stoichiometry of LC and HC genes of antibody fragment at shake-flask and bioreactor scale. rHu biosimilar Ranibizumab was selected as a model protein for the study. Expression stoichiometry of HC and LC gene at mRNA level was studied using RTqPCR, whereas protein expression level was studied quantitatively using RP-HPLC and SDS-PAGE analysis. In the case of dual promoter expression construct, it was observed that LC gene cloned in the MCS1 of the duet vectors has > 2-fold expression than the HC gene, cloned in the MCS2. Transcript abundance profile of the HC and LC genes determined at different time intervals post-induction shows a difference in the gene expression at the transcriptional level. Comparative analysis of dual promoter and co-transformation strategy shows better stoichiometry in co-transformation (1:1.3), whereas higher protein yield in a dual expression system (>2.4 fold). The use of lactose and galactose as inducers show higher Fab yield of 2.30 +/- 0.03 g/L and 2.81 +/- 0.06 g/L with expression stoichiometry of 1:1.9 and 1:2 (HC: LC) respectively than IPTG-based induction with a protein yield of 1.40 +/- 0.02 g/L.
Keywords: Dual promoter vector; Expression stoichiometry; High cell density fermentation; rHu biosimilar Ranibizumab; Transcript abundance

Behavioral and proteomic studies reveal methylglyoxal activate pathways associated with alzheimer’s disease - Patil, Gouri; Kulsange, Shabda; Kazi, Rubina; Chirmade, Tejas; Kale, Vaikhari; Mote, Chandrashekhar; Aswar, Manoj; Koratkar, Santosh; Agawane, Sachin; Kulkarni, Mahesh (ACS Pharmacology & Translational Science, 2022)
Diabetes is one of the major risk factors for Alzheimer’s disease (AD) development. The role of elevated levels of glucose, methylglyoxal (MGO), and advanced glycation end products (AGEs) in the pathogenesis of AD is not well understood. In this pursuit, we studied the role of methylglyoxal in the pathogenesis of AD in rat models. The elevated plus-maze (EPM) behavioral study indicated that MGO induces anxiety. Treatment of telmisartan (RAGE expression inhibitor) and aminoguanidine (MGO quencher) attenuated MGO induced anxiety. Further, hippocampal proteomics demonstrated that MGO treated rats differentially regulate proteins involved in calcium homeostasis, mitochondrial functioning, and apoptosis, which may affect neurotransmission and neuronal plasticity. The hippocampal tau phosphorylation level was increased in MGO treated rats, which was reduced in the presence of aminoguanidine and telmisartan. The plasma fructosamine level was increased upon MGO treatment. Hippocampal histochemistry showed vascular degeneration and neuronal loss upon MGO treatment. This study provides mechanistic insight into the role of MGO in the diabetes-associated development of AD.

Comparative analysis and structural modeling of elaeis oleifera FAD2, a fatty acid desaturase involved in unsaturated fatty acid composition of american oil palm - Ben Ayed, Rayda; Chirmade, Tejas; Hanana, Mohsen; Khamassi, Khalil; Ercisli, Sezai; Choudhary, Ravish; Kadoo, Narendra; Karunakaran, Rohini (Biology-Basel, 2022)
Simple Summary Palm oil has become the world's most important vegetable oil in terms of production quantity, and its overall demand is exponentially growing with the global population. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing palm oil quality. In this study, we focused on FAD2, a fatty acid desaturase enzyme involved in the desaturation and conversion of oleic acid to linoleic acid in Elaeis oleifera, identified through in silico annotation analysis. Our phylogenetic and comparative studies revealed two SNP markers, SNP278 and SNP851, significantly correlated with the oleic/linoleic acid contents. Our study provides fundamental insights into the mechanism of fatty acids synthesis in oil palm and could support the application of molecular biology techniques to enhance the enzymatic activity and substrate affinity of EoFAD2. American oil palm (Elaeis oleifera) is an important source of dietary oil that could fulfill the increasing worldwide demand for cooking oil. Therefore, improving its production is crucial and could be realized through breeding and genetic engineering approaches aiming to obtain high-yielding varieties with improved oil content and quality. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing oil quality. Our work focused on a fatty acid desaturase (FAD) enzyme involved in the desaturation and conversion of oleic acid to linoleic acid. Following the in silico identification and annotation of Elaeis oleifera FAD2, its molecular and structural features characterization was performed to better understand the mechanistic bases of its enzymatic activity. EoFAD2 is 1173 nucleotides long and encodes a protein of 390 amino acids that shares similarities with other FADs. Interestingly, the phylogenetic study showed three distinguished groups where EoFAD2 clustered among monocotyledonous taxa. EoFAD2 is a membrane-bound protein with five transmembrane domains presumably located in the endoplasmic reticulum. The homodimer organization model of EoFAD2 enzyme and substrates and respective substrate-binding residues were predicted and described. Moreover, the comparison between 24 FAD2 sequences from different species generated two interesting single-nucleotide polymorphisms (SNPs) associated with the oleic/linoleic acid contents.
Keywords: FAD2; Fatty acids; in silico annotation; linoleic acid ratio; oil palm; oleic; SNP; structural modeling

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.

Understanding unfolding and refolding of the antibody fragment (Fab) III: mapping covalent and non-covalent interactions during in-vitro refolding of light chain, heavy chain, and Fab. - Gani, Kayanat; Chirmade, Tejas; Ughade, Santosh; Thulasiram, Hirekodathakallu; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
In-vitro refolding of the antibody fragments from inclusion bodies is a critical manufacturing bottleneck. We have previously reported that Fab refolding involves the formation of an intermediate. To further decode the refolding pathway, we have mapped the covalent and non-covalent interactions during in-vitro refolding of individual light chain (LC), heavy chain (HC), and intact Fab. Intrinsic fluorescence analysis was performed to map the non -covalent interactions, whereas time-dependent disulfide mapping was performed using LC-MS/MS analysis under non-reducing and reducing atmospheres. Refolding of purified LC, HC, and intact Fab (Biosimilar rHu Ranibi-zumab) was investigated in the study. Under the reducing condition, LC, HC, and intact Fab required around 96, 30, and 70 h, respectively, whereas, under non-reducing conditions, they required only 48, 10, and 48 h, respectively, to acquire the native conformation. The disulfide bond mapping revealed that the bond between LC_Cys23/Cys88 is more unstable. The peptides mapped with the inter-chain disulfide bond were identified at 48 h during the refolding and can be considered as the rate-limiting step in (Fab) refolding. We have also studied a new refolding strategy involving assembly of separately refolded LC and HC into Fab molecule. In this case the Fab refolding yield was low (18.0 +/- 1.36%), indicating inefficient assembly of refolded LC and HC chain into native Fab molecule.
Keywords: Antibody fragment; Disulfide bond formation; In-vitro refolding; Light and heavy chain; rHu Ranibizumab

Understanding unfolding and refolding of the antibody fragments (Fab). II. Mapping intra and inter-chain disulfide bonds using mass spectrometry - Nainwal, Neeraj; Chirmade, Tejas; Gani, Kayanat; Rana, Sunil; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
Disulfide bond formation in recombinant protein therapeutics has a significant impact on the integrity and biological activity of the drug product. Formation of the disulfide linkage is the key rate-limiting step in in vitro refolding and overall manufacturing of the antibody fragments (Fab). This investigation is focused on mapping the intra, and inter-chain disulfide bonds in the in vitro refolded antibody fragments by using mass spectrometry (MS). Biosimilar rHu Ranibizumab and rHu Certolizumab expressed using E. coli were selected for the study. Both Fabs contain ten cysteine residues leading to two intra-chain disulfide bonds on each subunit and a single interchain disulfide linkage. rHu Certolizumab has an additional cysteine which is unpaired and used for pegylation. The amino acid sequence in the disulfide-bonded peptides was confirmed by Collision-induced dissociation (CID), Electron transfer dissociation (ETD) and High-energy collision dissociation (HCD). The light chain (LC) intra-chain disulfide is formed between Cys23-Cys88 and Cys134-Cys194 in both the Fabs. The heavy chain (HC) intra-chain disulfides are formed between Cys22-Cys96 and Cys150-Cys206 in rHu Ranibizumab. LC and HC subunits of rHu Ranibizumab are covalently linked by disulfide linkage formed between Cys214 of LC and Cys226 of HC. This study suggests that information from multiple MS platforms and orthogonal methods for peptide fragmentation can be effectively used to map disulfide linkages in biosimilar therapeutic proteins.
Keywords: Antibody fragments (Fab); Collision-induced dissociation; Electron transfer dissociation; High-energy collision dissociation; in vitro refolding; Ranibizumab

Cloning and expression of antibody fragment (Fab) II: Effect of expression hosts on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Nainwal, Neeraj; Bhambure, Rahul (Biochemical Engineering Journal, 2023)
Protein expression stoichiometry of individual subunits plays a critical role in the formation of multi-domain functional therapeutic proteins like antibody fragments. In this study, we have evaluated light to heavy chain ratio (LC: HC) of rHu Ranibizumab expressed using duet expression vector in six E. coli strains. The LC: HC ratio at the protein level was determined using RP-HPLC whereas transcript abundance of LC and HC at the mRNA level was determined using RTqPCR. Protein level study as well as the transcript abundance profiles of the LC and HC genes were observed to be differentially expressed across the E. coli strains. BL21 STAR (DE3) and Origami 2 strains resulted in a nearly equal expression ratio of LC and HC genes. Untargeted shotgun proteomics analysis was performed to identify the differentially expressed proteins. Total 1083 proteins were identified in the spectral IDA library, while 244 and 149 proteins were differentially expressed in Origami 2 and BL21 STAR (DE3) respectively. These proteins are associated with translation and nucleotide biosynthesis pathways. Ob-tained results provide insights into the impact of different E.coli host strains on LC: HC ratio, the probable reasons behind the unbalanced gene ratio, and provide useful transcriptomic and proteomics analysis protocols.
Keywords: E.coli host strains; Expression stoichiometry; Proteome analysis; rHu biosimilar Ranibizumab; Transcript abundance